Corruption, Road Infrastructure Quality and Income Inequality - Wijayanti, Shinta; khoirunurrofik, khoirunurrofik (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 2, Agustus 2022 (pp.162-339), 2022)
This study investigates the relationship between the corruption cases in road infrastructure and the quality of road infrastructure and its effect on income inequality in Indonesia. Using actual data on cases of road infrastructure corruption that have been in court and a fixed-effect data panel estimation model with standard errors clustered by island regions in Indonesia, this study shows a significant negative correlation between road infrastructure corruption cases and road infrastructure quality. This study also found a significant positive correlation between cases of road infrastructure corruption and income inequality moderated by economic growth. The finding indicates that the more corruption cases occur in an area, the lower the quality of road infrastructure and the increasing income inequality as measured by the Gini index (gini ratio).